Left Ventricular Long-Axis Function Assessed with Cardiac Cine MR Imaging Is an Independent Predictor of All-Cause Mortality in Patients with Reduced Ejection Fraction: A Multicenter Study - Romano, Simone (Radiology, 2018)
PURPOSE: To evaluate the prognostic value of a simple index of left ventricular (LV) long-axis function—lateral mitral annular plane systolic excursion (MAPSE)—in a large multicenter population of patients with reduced ejection fraction (EF) who were undergoing cardiac magnetic resonance (MR) imaging. MATERIALS AND METHODS: This retrospective study included 1040 consecutive patients (mean age, 59.5 years ± 15.8) at four U.S. medical centers who were undergoing cardiac MR imaging for assessment of LV dysfunction with EF less than 50%. Lateral MAPSE was measured in the four-chamber cine view. The primary end point was all-cause death. Cox proportional hazards regression modeling was used to examine the independent association between lateral MAPSE and death. The incremental prognostic value of lateral MAPSE was assessed in nested models. RESULTS: During a median follow-up of 4.4 years, 132 patients died. With Kaplan-Meier analysis, the risk of death increased significantly with decreasing tertiles of lateral MAPSE (log-rank P = .0001). Patients with relatively preserved lateral MAPSE (>9 mm) had very few deaths, regardless of whether their EF was above or below 35%. Patients with late gadolinium enhancement (LGE) and low lateral MAPSE had significantly reduced survival compared to those with LGE and high lateral MAPSE (log-rank P < .0001). Lateral MAPSE was independently associated with risk of death after adjustment for clinical and imaging risk factors, which were univariate predictors (age, body mass index, diabetes, LV end-diastolic volume index, LGE, EF) (hazard ratio = 2.051 per mm decrease; 95% confidence interval [CI]: 1.520, 2.768; P < .001). Inclusion of lateral MAPSE in this model resulted in significant improvement in model fit (likelihood ratio test P < .0001) and C statistic (increasing from 0.675 to 0.844; P < .0001). Continuous net reclassification improvement was 1.036 (95% CI: 0.878, 1.194). CONCLUSION: Lateral MAPSE measured during routine cine cardiac MR imaging is a significant independent predictor of mortality in patients with LV dysfunction, incremental to common clinical and cardiac MR risk factors—including EF and LGE. (©) RSNA, 2017